Effect of Mixing Sequence on Green Concrete Using Artifical Coarse Aggregate - Silvia T. Romadhona; Januarti J. Ekaputri (Institut Teknologi Sepuluh Nopember (ITS), 2024)
The mixing method for green concrete with a mixture of Ground Granulated Blast Furnace Slag (GGBFS), Fly Ash and artificial coarse aggregate is an important thing that needs special attention to achieve a uniform mixture of materials. Testing the effect of the mixing sequence was carried out to obtain the optimum mixing sequence for the green concrete mixture. The experiment was carried out using 4 different methods, namely a combination of 25% fly ash, 25% GGBFS and 25% artificial coarse aggregate with different mixing sequences for cement material, coarse aggregate, fine aggregate, artificial aggregate as well as water and admixture dosages. Test results based on workability parameters, slump loss, compressive strength, split tensile strength, concrete shrinkage and heat of hydration show that mixing method 4 has 5% higher compressive strength resultsthan other methods, and produces optimum workability and slump loss. Concrete mixed with GGBFS, Fly Ash and artificial coarse aggregate can reduce the heat of hydration by 15%. Artificial coarse aggregate reduces compressive strength by7%, but has better concrete shrinkage.